Improving the Ability to Analyze the Values of Ikayat Texts Using the Sharing Reading Literacy Learning Model for Grade X Students at SMA Negeri 2 Padangsidimpuan - Samosir, Yola Agriani; Hasibuan, Nikmah Sari; Harahap, Eli Marlina; Khairunnisah, Khairunnisah (Westscience Press, 2025)
The low ability of students in analyzing values in fable texts is influenced by several factors such as reading interest, difficulty understanding and digesting important information in reading and difficulty in conveying the contents of the reading that has been read. This study aims to improve the ability to analyze the values of fable texts using the Sharing Reading Literacy learning model in class X students of SMA Negeri 2 Padangsidimpuan. This study uses a classroom action research (CAR) method which is implemented in stages starting from the design, implementation, observation, and reflection stages. The subjects in this study were 35 class X students. The results of this study indicate that the Sharing Reading Literacy learning model can improve students' ability to analyze values in fable texts. This is evidenced by the increase in student learning outcomes from before being given the action and the second stage after being given the class action to 85. Student effectiveness in learning activities also increased with student involvement in the learning process. The application of the Sharing Reading Literacy learning model has proven effective in improving the ability to analyze the values of fable texts in class X students of SMA Negeri 2 Padangsidimpuan. It is hoped that the results of this study can be a reference for further research related to classroom action research that can create effective learning strategies.